Investigation of coumarin functionality on the formation of polymeric nanoparticles - Chung, Jae Woo; Neikirk, Colin; Priestley, Rodney D. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
The effect of coumarin molecules on the formation of polymeric nanoparticles is examined using a model polymer, poly(methyl methacrylate) (PMMA), functionalized with varying amounts of coumarin pendant groups (PCM). PCM nanoparticles are prepared in a continuous manner by Flash NanoPrecipitation (FNP). PCM forms spherical nanoparticles in water, while the PMMA without coumarin functionality fails to form nanoparticles. As the amount of coumarin functionality increases, the nanoparticle size and size polydispersity are decreased and the nanoparticle stability in water is enhanced. In particular, well-isolated spherical nanoparticles are generated from PCM with 20 mol% coumarin side chain functionality. These results can be explained by an observed increase in the negative surface charge with increasing coumarin content in the polymer. (C) 2013 Elsevier Inc. All rights reserved.